THE EFFECT OF FINANCIAL PERFORMANCE ON COMPANY VALUE OF PT YAKULT SEREMBAN SDN., BHD WITH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AS A MODERATING VARIABLE - Sri Mulyani; Nunik Nurmalasari (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
The purpose of this study is to examine the effect of financial performance (ROA) toward the corporate value and to examine the effect of cost allocation of corporate social responsibility (CSR) in moderating the relationships of financial performance toward the corporate value of Yakult Seremban SDN., BHD. In the analysis of the data, multiple regretion analysis is used to determine the effect of variables involved in this study. The results of the study show that partially financial performance (ROA) does not significantly affect the corporated value. Furthermore, corporate social responcibility does not to partially moderate the effect of the financial performance relationships toward corporate value. This research uses descriptive verification research with quantitative approach. The data used secondary data sourced from the annual report yakutl honsha., CO.BHD. population of yakult honsha financial report research, with sample 2014-2018 financial statements. the variables in this study are independent, independent and moderating variables.